PERSEPSI ORANG TUA TERHADAP PENDIDIKAN ANAK USIA DINI DI DESA PARIT BARU - Trisnaningsih, Sry; Fadillah, Fadillah; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to obtain an overview to analyze how Parents 'Perceptions of Early Childhood Education in Parit Baru Village, Sungai Raya District, Kubu Raya District, and how parents' knowledge (cognitive aspects) about early childhood education, and how the impression or feeling ( Affective aspects) parents about early childhood education. and How parents' actions or behaviors (conative aspects) of early childhood education. The method used in this study is descriptive method with a quantitative approach. The location of this study was in the village of Parit Baru, Sungai Raya District, Kubu Raya Regency. Data collection techniques and tools use interviews and documentation studies. Data analysis techniques use data reduction, data display, withdrawal and verification. Data collection in this study uses interviews. Based on the conclusion of the interview results in general it can be concluded that parents' perceptions of early childhood education are determined by cognitive aspects in the form of knowledge and experience of parents, affective aspects namely the impression of parents, and the conative aspects of motivation or actions of parents.Keywords: Perceptions, Parents